1943
DOI: 10.1111/j.1939-0025.1943.tb05983.x
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus and children's personality reactions.

Abstract: ANY physical handicaps have been described and classified as to anatom-M ical and physiological characteristics, but little emphasis has been put on the person who experiences the handicap and how it is experienced. Strabismus interested us, among other reasons, because it is a common defect which is correctable to a large degree. This lends itself to a study of the personal and social adjustments of the individual before and after the defect.A search of our medical records uncovered ten cross-eyed children in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1947
1947
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The results of this study indicate that the actual strabismus is not a factor in a child's selection of a playmate however, caution is necessary when trying to extrapolate to a real life situation. Children with strabismus may adopt certain undesirable characteristics as a result of their condition, such as avoiding eye contact and becoming introverted or shy (Lion et al, 1943;Groffman, 1978). Perhaps these personality traits would decrease peer acceptance of a child with strabismus although their eye alignment on its own would not have the same effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study indicate that the actual strabismus is not a factor in a child's selection of a playmate however, caution is necessary when trying to extrapolate to a real life situation. Children with strabismus may adopt certain undesirable characteristics as a result of their condition, such as avoiding eye contact and becoming introverted or shy (Lion et al, 1943;Groffman, 1978). Perhaps these personality traits would decrease peer acceptance of a child with strabismus although their eye alignment on its own would not have the same effect.…”
Section: Discussionmentioning
confidence: 99%
“…Older literature based on case reports has suggested that children with strabismus encounter difficulty with social interaction among their peers in the elementary school years (Lion et al, 1943). A more recent study by Paysse et al (2001) supported these findings and reported that negative attitudes toward strabismus emerge around the age of six.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] Very often, these children are embarrassed about their condition, have difficulty making eye contact, and have problems with self-esteem. 9 Such negative impact appears to persist into adulthood and can adversely influence one's social skills, 10 psychological health, 11,12 and employability.…”
mentioning
confidence: 98%
“…As early as 1943, Lion et al 1 wrote on the topic of strabismus and its adverse effects on children’s personalities. However, the first major research study evaluating the psychosocial aspects of strabismus was performed by Satterfield et al in 1993.…”
mentioning
confidence: 99%